Analisis Sentimen Twitter Terpilihnya Prabowo - Gibran Menggunakan Metode Neural Network - Diana Dwi Rahayu; Muhammad Fatchan; Alfonsus Ligouri (TEMATIK, 2024)
One of the most important elections in Indonesian democracy is the presidential election, which chooses the country's leader for the next five years. In the 2024 presidential election, there are three candidates for president and vice president, including the Prabowo Subianto - Gibran Rakabuming Raka pair. The election process has taken centre stage on social media, particularly Twitter, where people interact, share information, and express their opinions and feelings. This study aims to look at public opinion towards the Prabowo-Gibran team, which has attracted a lot of attention since Gibran was nominated as a vice presidential candidate until he was declared the winner in the 2024 presidential election by the KPU. This analysis provides valuable insight into understanding public opinion and feelings towards the president and vice president-elect. The method used in this research is neural network (NN), which is proven to be effective in text data classification and capable of producing high accuracy. The dataset used is public opinion on Twitter, which is taken through the data crawling process. The initial data of 1511 tweets was then cleaned and prepared into a dataset of 1500 tweets, with the main attribute being the content of the tweet. Based on the findings, the neural network model created was able to classify the sentiment of tweets related to the Prabowo-Gibran pair with an accuracy rate of 93%. Thus, this sentiment analysis makes an important contribution to understanding the public's response to the presidential election process and the election of a new president and vice president